Pengaruh Model Pembelajaran Game Based Learning Terhadap Hasil Belajar Dan Retensi Hasil Belajar Siswa Kelas V MIS Al-Hudzaifah Dobo: Indonesia - Djamiri, Tasqia Temarwut; Leasa, Marleny; Talakua, Melvie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the existence and influence of game-based learning models on the learning outcomes and retention of learning outcomes of fifth-grade students at MIS Al-Hudzaifah Dobo. The research method used in this study was experimental research using quasi-experiments. The results showed that there was an influence of game-based learning models on the learning outcomes and retention of learning outcomes of MIS Al-Hudzaifah Dobo students